Double-layer polymer solid electrolyte, preparation method thereof and lithium ion battery

By using a double-layer polymer solid electrolyte in lithium-ion batteries, the problem of insufficient safety performance of liquid electrolytes is solved, and a battery with high circulation performance and capacity is achieved, enhancing the overall safety of the battery.

CN119518083AActive Publication Date: 2025-02-25SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411706455.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The liquid electrolytes used in existing lithium-ion batteries have problems such as high toxicity, easy leakage, flammability and explosion, and have poor compatibility with lithium metal, resulting in insufficient safety performance.

Method used

Using a double-layer polymer solid electrolyte, the first polymer solid electrolyte layer and the second polymer solid electrolyte layer are stacked and the second polymer solid electrolyte layer are in contact with the positive electrode and the negative electrode of the battery respectively. The electrochemical window and ionic conductivity are improved by using a composite system of specific components, and are compatible with high voltage positive electrode and low voltage lithium metal negative electrode.

Benefits of technology

The high circulation performance and capacity of lithium-ion batteries are achieved, while the safety performance of the batteries is improved, avoiding the danger of liquid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518083A_ABST
    Figure CN119518083A_ABST
Patent Text Reader

Abstract

The invention provides a double-layer polymer solid electrolyte, a preparation method thereof and a lithium ion battery, and belongs to the technical field of solid electrolyte manufacturing. The first polymer solid electrolyte layer comprises the following raw materials in parts by weight: 4-30 parts of a first reactive monomer A, 5-25 parts of a first reactive monomer B, a first cross-linking agent, a first photoinitiator, a first lithium salt, 1-20 parts of a first carbonic ester plasticizer and 20-45 parts of a nitrile plasticizer; the second polymer solid electrolyte layer comprises the following raw materials in parts by weight: 4-30 parts of a second reactive monomer A, 5-25 parts of a second reactive monomer B, a second cross-linking agent, a second photoinitiator, a second lithium salt, 1-35 parts of a second carbonic ester plasticizer and 10-35 parts of a fluorine-containing plasticizer; the double-layer polymer solid electrolyte has the advantages of relatively high ionic conductivity and compatibility of a high-voltage battery positive electrode and a low-voltage lithium metal negative electrode, so that the corresponding battery has relatively excellent cycle performance and relatively high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid electrolyte manufacturing, and in particular to a double-layer polymer solid electrolyte and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries are selected as a green energy storage device for their high energy density, long service life and environmental friendliness, and have successfully dominated the energy storage and power equipment market. At present, graphite is often used as the negative electrode of lithium-ion batteries, which is prone to damage during the charging and discharging process, reducing its capacity, which also limits the development of higher energy density. The high specific capacity of lithium metal (3860mAh / g) can easily break this barrier. However, organic solvents are mainly used as electrolytes in commercial lithium-ion batteries, but they have problems such as high toxicity, easy leakage, and flammability. More importantly, they have poor compatibility with lithium metal. When in contact with lithium metal, a large number of dendrites will be generated. The growth of lithium dendrites can easily pierce the diaphragm and cause battery short circuit, which will bring serious safety problems. At the same time, the active substances in the positive electrode material will also dissolve and shuttle to the negative electrode, causing a decrease in capacity. Therefore, using non-flammable solid electrolytes instead of liquid electrolytes is one of the important ways to solve the safety performance of lithium-ion batteries, which has also become one of the important technical development directions for the next generation of batteries.

[0003] In the prior art, the research on solid electrolytes mainly includes inorganic ceramic electrolytes and organic polymer electrolytes. Both of these solid electrolytes have relatively high low-voltage stability and are expected to match metal lithium negative electrodes. Among them, polymer solid electrolytes have good flexibility and can maintain good contact with the interface between electrodes, so that they have the advantage of low interface impedance, and they are also easy to process and form, which is convenient for industrialization; however, due to unreasonable design, existing polymer solid electrolytes have low ion conductivity and are difficult to be compatible with high-voltage battery positive electrodes and low-voltage lithium metal negative electrodes, which in turn affects the cycle performance and capacity of the corresponding batteries. Summary of the invention

[0004] The purpose of the present application is to provide a double-layer polymer solid electrolyte and a preparation method thereof, and a lithium-ion battery. The double-layer polymer solid electrolyte has the advantages of high ionic conductivity and compatibility with high-voltage battery positive electrodes and low-voltage lithium metal negative electrodes, so that the corresponding battery has relatively excellent cycle performance and higher capacity.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, an embodiment of the present application provides a double-layer polymer solid electrolyte, comprising a first polymer solid electrolyte layer for contacting a positive electrode and a second polymer solid electrolyte layer for contacting a negative electrode, which are stacked and distributed; in terms of weight percentage, the raw materials of the first polymer solid electrolyte layer include: 4 to 30 parts of a first reaction monomer A, 5 to 25 parts of a first reaction monomer B, 2 to 10 parts of a first cross-linking agent, 0.1 to 1.1 parts of a first photoinitiator, 5 to 15 parts of a first lithium salt, 1 to 20 parts of a first carbonate plasticizer, and 20 to 45 parts of a nitrile plasticizer; in terms of weight percentage, the raw materials of the second polymer solid electrolyte layer include: 4 to 30 parts of a second reaction monomer A, 5 to 25 parts of a second reaction monomer B, 2 to 10 parts of a first cross-linking agent, 0.1 to 1.1 parts of a first photoinitiator, 5 to 15 parts of a first lithium salt, 1 to 20 parts of a first carbonate plasticizer, and 20 to 45 parts of a nitrile plasticizer. 5 to 25 parts, a second cross-linking agent 2 to 10 parts, a second photoinitiator 0.1 to 1.1 parts, a second lithium salt 5 to 15 parts, a second carbonate plasticizer 1 to 35 parts and a fluorine-containing plasticizer 10 to 35 parts; wherein the first reaction monomer A and the second reaction monomer A are both acrylate monomers containing ethoxy groups, and the first reaction monomer B and the second reaction monomer B are both acrylate monomers containing fluorinated groups.

[0007] In the above technical solution, the polymer solid electrolyte has a double-layer structure. Specifically, the first polymer solid electrolyte layer is used to contact the positive electrode, and its preparation raw materials are composed of specific components in specific mass fractions. On the one hand, the plasticizer is composed of a carbonate plasticizer and a nitrile plasticizer. This composite system plasticizer enables the first polymer solid electrolyte layer to have a higher electrochemical window, so that the first polymer solid electrolyte layer can be better adapted to the high-voltage positive electrode; in addition, this composite system plasticizer enables the first polymer solid electrolyte layer to have a higher ionic conductivity; on the other hand, the reaction monomer is composed of an acrylate monomer containing an ethoxy group and an acrylate monomer containing a fluorinated group. This composite system reaction monomer also enables the first polymer solid electrolyte layer to have a higher ionic conductivity. The second polymer solid electrolyte layer is used to contact the negative electrode, and its preparation raw materials are composed of specific components according to specific mass fractions. On the one hand, the plasticizer is composed of a carbonate plasticizer and a fluorine-containing plasticizer. This composite system plasticizer enables the second polymer solid electrolyte layer to be well adapted to the low-voltage negative electrode and also contributes to the formation of the SEI film on the negative electrode side; in addition, this composite system plasticizer enables the second polymer solid electrolyte layer to have a higher ionic conductivity; on the other hand, the reaction monomer is composed of an acrylate monomer containing an ethoxy group and an acrylate monomer containing a fluorinated group. This composite system reaction monomer also enables the second polymer solid electrolyte layer to have a higher ionic conductivity. The double-layer polymer solid electrolyte provided in the embodiment of the present application has the advantages of high ionic conductivity and compatibility with high-voltage battery positive electrodes and low-voltage lithium metal negative electrodes, so that the corresponding battery has relatively excellent cycle performance and higher capacity.

[0008] In some optional embodiments, the nitrile plasticizer is selected from at least one of succinonitrile, adiponitrile, tetracyanoethylene, ethylene glycol dipropionitrile ether, sulfonyl dipropionitrile, 1,3,6-hexanetrinitrile and 1,2,5-pentanetrinitrile.

[0009] In the above technical scheme, there are many types of nitrile plasticizers applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical scheme provided by the embodiments of the present application; in addition, specific types of nitrile plasticizers can be better compounded with carbonate plasticizers to make the first polymer solid electrolyte layer have higher ionic conductivity and be better adapted to the positive electrode.

[0010] In some optional embodiments, the fluorine-containing plasticizer is selected from at least one of fluoroethylene carbonate, ethyl trifluoroacetate, trifluoroethyl trifluoroacetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorinated methanesulfonimide, difluoroethane and fluorinated malonate.

[0011] In the above technical solutions, there are many types of fluorinated plasticizers applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided by the embodiments of the present application; in addition, specific types of fluorinated plasticizers can be better compounded with carbonate plasticizers to make the second polymer solid electrolyte layer have higher ionic conductivity and be better adapted to the negative electrode.

[0012] In some optional embodiments, the first carbonate plasticizer and the second carbonate plasticizer are independently selected from at least one of ethylene carbonate, vinylene carbonate, dimethyl carbonate, dipropyl carbonate, ethylene carbonate, butylene carbonate, ethyl methyl carbonate and propylene carbonate.

[0013] In the above technical solutions, there are many types of fluorinated plasticizers applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided by the embodiments of the present application.

[0014] In some optional embodiments, the first reactive monomer A and the second reactive monomer A are independently selected from at least one of ethoxyethyl acrylate, ethoxylated tetrahydrofuran acrylate, ethoxylated trimethylol triacrylate, 3-ethoxyethyl acrylate, 2-phenoxyethyl acrylate and 2-vinyloxyethoxy acrylate.

[0015] In the above technical scheme, there are many types of reactive monomers A applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical scheme provided by the embodiments of the present application; in addition, the polymer skeleton formed by a specific type of reactive monomer A has a higher ionic conductivity.

[0016] In some optional embodiments, the first reactive monomer B and the second reactive monomer B are independently selected from at least one of hexafluorobutyl acrylate, tetrafluoropropyl acrylate, trifluoroethyl acrylate, dodecafluoroheptyl methacrylate, perfluoroalkylethyl acrylate and N-methylperfluorohexylsulfonamide ethyl acrylate.

[0017] In the above technical scheme, there are many types of reactive monomers B applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical scheme provided by the embodiments of the present application; in addition, the polymer skeleton formed by a specific type of reactive monomer B has a higher ionic conductivity.

[0018] In some optional embodiments, the double-layer polymer solid electrolyte satisfies at least one of the following conditions (1) to (3):

[0019] (1) The first crosslinking agent and the second crosslinking agent are independently selected from at least one of diethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate and ethoxylated bisphenol diacrylate.

[0020] (2) The first photoinitiator and the second photoinitiator are independently selected from at least one of 2,2-dimethoxy-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl chloride-diphenylphosphine oxide, 2,2-dimethoxy-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0021] (3) The first lithium salt and the second lithium salt are independently selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium hexafluorophosphide, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(difluorosulfonyl)imide.

[0022] In the above technical solutions, there are many types of cross-linking agents, photoinitiators and lithium salts applicable to the embodiments of the present application, which can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided by the embodiments of the present application.

[0023] In a second aspect, an embodiment of the present application provides a method for preparing a double-layer polymer solid electrolyte as provided in an embodiment of the first aspect, comprising the following steps:

[0024] The first reaction monomer A, the first reaction monomer B, the first lithium salt and a part of the first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, the first crosslinking agent, another part of the first photoinitiator, the first carbonate plasticizer and the nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain a first polymer solid electrolyte layer. The second reaction monomer A, the second reaction monomer B, the second lithium salt and a part of the second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, the second crosslinking agent, another part of the second photoinitiator, the second carbonate plasticizer and the fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is applied to the surface of the first polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain a double-layer polymer solid electrolyte layer.

[0025] Alternatively, the second reaction monomer A, the second reaction monomer B, the second lithium salt and a part of the second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, the second crosslinker, another part of the second photoinitiator, the second carbonate plasticizer and the fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain a second polymer solid electrolyte layer. The first reaction monomer A, the first reaction monomer B, the first lithium salt and a part of the first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, the first crosslinker, another part of the first photoinitiator, the first carbonate plasticizer and the nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is applied to the surface of the second polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain a double-layer polymer solid electrolyte layer.

[0026] In the above technical solution, ultraviolet light curing is used to prepare a double-layer polymer solid electrolyte, and no volatile solvents are used, which has the advantages of safety and environmental protection. At the same time, it also has the advantages of low preparation cost and high preparation efficiency. In addition, there are many specific process forms (the first polymer solid electrolyte layer can be prepared first, or the second polymer solid electrolyte layer can be prepared first), which can provide more feasible implementation methods.

[0027] In some optional embodiments, the first mixed solution is placed under ultraviolet light for reaction until the viscosity of the first mixed solution is 10000-15000 mPa.s; and / or, the second mixed solution is placed under ultraviolet light for reaction until the viscosity of the second mixed solution is 10000-15000 mPa.s.

[0028] In the above technical solution, during the curing reaction of the mixed solution under ultraviolet light, the viscosity of the mixed solution reaches a set range, so that the corresponding polymer solid electrolyte layer prepared has a relatively ideal ionic conductivity.

[0029] In a third aspect, an embodiment of the present application provides a lithium-ion battery, comprising a double-layer polymer solid electrolyte provided in the embodiment of the first aspect, wherein the first polymer solid electrolyte layer is in contact with the positive electrode of the battery, and the second polymer solid electrolyte layer is in contact with the negative electrode of the battery.

[0030] In the above technical solution, the lithium-ion battery includes a double-layer polymer solid electrolyte as provided in the first aspect embodiment, wherein the double-layer polymer solid electrolyte has high ionic conductivity and is compatible with a high-voltage battery positive electrode and a low-voltage lithium metal negative electrode, so that the battery has relatively excellent cycle performance and higher capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A schematic diagram of the structure of a double-layer polymer solid electrolyte provided in an embodiment of the present application.

[0033] Icon: 10 - double-layer polymer solid electrolyte; 100 - first polymer solid electrolyte layer; 200 - second polymer solid electrolyte layer. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0035] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.

[0036] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values ​​"a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".

[0037] A double-layer polymer solid electrolyte and a preparation method thereof according to an embodiment of the present application are described in detail below.

[0038] In a first aspect, an embodiment of the present application provides a double-layer polymer solid electrolyte, comprising a first polymer solid electrolyte layer for contacting a positive electrode and a second polymer solid electrolyte layer for contacting a negative electrode, which are stacked and distributed; in terms of weight percentage, the raw materials of the first polymer solid electrolyte layer include: 4 to 30 parts of a first reaction monomer A, 5 to 25 parts of a first reaction monomer B, 2 to 10 parts of a first cross-linking agent, 0.1 to 1.1 parts of a first photoinitiator, 5 to 15 parts of a first lithium salt, 1 to 20 parts of a first carbonate plasticizer, and 20 to 45 parts of a nitrile plasticizer; in terms of weight percentage, the raw materials of the second polymer solid electrolyte layer include: 4 to 30 parts of a second reaction monomer A, 5 to 25 parts of a second reaction monomer B, 2 to 10 parts of a first cross-linking agent, 0.1 to 1.1 parts of a first photoinitiator, 5 to 15 parts of a first lithium salt, 1 to 20 parts of a first carbonate plasticizer, and 20 to 45 parts of a nitrile plasticizer. 5 to 25 parts, a second cross-linking agent 2 to 10 parts, a second photoinitiator 0.1 to 1.1 parts, a second lithium salt 5 to 15 parts, a second carbonate plasticizer 1 to 35 parts and a fluorine-containing plasticizer 10 to 35 parts; wherein the first reaction monomer A and the second reaction monomer A are both acrylate monomers containing ethoxy groups, and the first reaction monomer B and the second reaction monomer B are both acrylate monomers containing fluorinated groups.

[0039] In the present application, the polymer solid electrolyte has a double-layer structure. Specifically, the first polymer solid electrolyte layer is used to contact the positive electrode, and its preparation raw materials are composed of specific components according to specific mass fractions. On the one hand, the plasticizer is composed of a carbonate plasticizer and a nitrile plasticizer. This composite system plasticizer enables the first polymer solid electrolyte layer to have a higher electrochemical window, so that the first polymer solid electrolyte layer can be better adapted to the high-voltage positive electrode; in addition, this composite system plasticizer enables the first polymer solid electrolyte layer to also have a higher ionic conductivity; on the other hand, the reaction monomer is composed of a composite of an acrylate monomer containing an ethoxy group and an acrylate monomer containing a fluorinated group. This composite system reaction monomer also enables the first polymer solid electrolyte layer to have a higher ionic conductivity. The second polymer solid electrolyte layer is used to contact the negative electrode, and its preparation raw materials are composed of specific components according to specific mass fractions. On the one hand, the plasticizer is composed of a carbonate plasticizer and a fluorine-containing plasticizer. This composite system plasticizer enables the second polymer solid electrolyte layer to be well adapted to the low-voltage negative electrode and also contributes to the formation of the SEI film on the negative electrode side; in addition, this composite system plasticizer enables the second polymer solid electrolyte layer to have a higher ionic conductivity; on the other hand, the reaction monomer is composed of an acrylate monomer containing an ethoxy group and an acrylate monomer containing a fluorinated group. This composite system reaction monomer also enables the second polymer solid electrolyte layer to have a higher ionic conductivity. The double-layer polymer solid electrolyte provided in the embodiment of the present application has the advantages of high ionic conductivity and compatibility with high-voltage battery positive electrodes and low-voltage lithium metal negative electrodes, so that the corresponding battery has relatively excellent cycle performance and higher capacity.

[0040] It should be emphasized that there are currently few related studies on double-layer polymer solid electrolytes, and in some of the relevant information that has been made public, the conventional optimization method used is mainly to use different types of polymers for the high-voltage positive electrode and the low-voltage negative electrode, respectively, in order to make them compatible with the high-voltage positive electrode and the low-voltage negative electrode. There are no reports on optimizing plasticizers to make them compatible with high-voltage positive electrodes and low-voltage negative electrodes. Furthermore, it is even more difficult to know what specific plasticizers to use to be compatible with high-voltage positive electrodes and low-voltage negative electrodes.

[0041] It should be noted that the types of the raw materials in the polymer solid electrolyte layer are not limited.

[0042] As an example, the nitrile plasticizer is selected from at least one of succinonitrile, adiponitrile, tetracyanoethylene, ethylene glycol dipropionitrile ether, sulfonyl dipropionitrile, 1,3,6-hexanetrinitrile and 1,2,5-pentanetrinitrile.

[0043] In this embodiment, there are many types of nitrile plasticizers that can be applied to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application; in addition, specific types of nitrile plasticizers can be better compounded with carbonate plasticizers to make the first polymer solid electrolyte layer have higher ionic conductivity and be better adapted to the positive electrode.

[0044] As an example, the fluorine-containing plasticizer is at least one selected from fluoroethylene carbonate, ethyl trifluoroacetate, trifluoroethyl trifluoroacetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorinated methanesulfonimide, difluoroethane and fluorinated malonate.

[0045] In this embodiment, there are many types of fluorine-containing plasticizers applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application; in addition, specific types of fluorine-containing plasticizers can be better compounded with carbonate plasticizers to make the second polymer solid electrolyte layer have higher ionic conductivity and be better adapted to the negative electrode.

[0046] As an example, the first carbonate plasticizer and the second carbonate plasticizer are independently selected from at least one of ethylene carbonate, vinylene carbonate, dimethyl carbonate, dipropyl carbonate, ethylene carbonate, butylene carbonate, ethyl methyl carbonate and propylene carbonate.

[0047] In this embodiment, there are many types of fluorine-containing plasticizers applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided by the embodiments of the present application.

[0048] As an example, the first reactive monomer A and the second reactive monomer A are independently selected from at least one of ethoxyethyl acrylate, ethoxylated tetrahydrofuran acrylate, ethoxylated trimethylol triacrylate, 3-ethoxyethyl acrylate, 2-phenoxyethyl acrylate and 2-vinyloxyethoxy acrylate.

[0049] In this embodiment, there are many types of reactive monomers A applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application; in addition, the polymer skeleton formed by a specific type of reactive monomer A has a higher ionic conductivity.

[0050] As an example, the first reactive monomer B and the second reactive monomer B are independently selected from at least one of butyl hexafluoroacrylate, propyl tetrafluoroacrylate, ethyl trifluoroacrylate, dodecafluoroheptyl methacrylate, perfluoroalkylethyl acrylate and N-methylperfluorohexylsulfonamide ethyl acrylate.

[0051] In this embodiment, there are many types of reactive monomers B applicable to the embodiments of the present application, and more feasible implementation plans can be provided, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application; in addition, the polymer skeleton formed by a specific type of reactive monomer B has a higher ionic conductivity.

[0052] As an example, the double-layer polymer solid electrolyte satisfies at least one of the following conditions (1) to (3):

[0053] (1) The first crosslinking agent and the second crosslinking agent are independently selected from at least one of diethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate and ethoxylated bisphenol diacrylate.

[0054] (2) The first photoinitiator and the second photoinitiator are independently selected from at least one of 2,2-dimethoxy-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl chloride-diphenylphosphine oxide, 2,2-dimethoxy-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0055] (3) The first lithium salt and the second lithium salt are independently selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium hexafluorophosphide, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(difluorosulfonyl)imide.

[0056] In this embodiment, there are many types of cross-linking agents, photoinitiators and lithium salts applicable to the embodiments of the present application, which can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application.

[0057] As an example, the thickness ratio of the first polymer solid electrolyte layer and the second polymer solid electrolyte layer is 1:(0.9~1.1), for example but not limited to, the thickness ratio of the two is any point value of 1:0.9, 1:1 and 1:1 or a range value between any two.

[0058] In this embodiment, the thicknesses of the two polymer solid electrolyte layers are set to be substantially the same, which can better enable compatibility between the high-voltage positive electrode and the low-voltage negative electrode.

[0059] It should be noted that the components and their mass ratios in the double-layer polymer solid electrolyte that are not particularly described or limited can be set according to conventional selections in the art.

[0060] See also Figure 1 As an example, the double-layer polymer solid electrolyte 10 includes a first polymer solid electrolyte layer 100 and a second polymer solid electrolyte layer 200 that are stacked.

[0061] In a second aspect, an embodiment of the present application provides a method for preparing a double-layer polymer solid electrolyte as provided in an embodiment of the first aspect, comprising the following steps:

[0062] A first reaction monomer A, a first reaction monomer B, a first lithium salt and a portion of a first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, a first crosslinking agent, another portion of the first photoinitiator, a first carbonate plasticizer and a nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain a first polymer solid electrolyte layer.

[0063] It should be noted that the sum of the masses of the two parts of the first photoinitiator is equal to the mass of the first photoinitiator in the raw material of the first polymer solid electrolyte layer.

[0064] A second reaction monomer A, a second reaction monomer B, a second lithium salt and a portion of a second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, a second crosslinking agent, another portion of the second photoinitiator, a second carbonate plasticizer and a fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is applied to the surface of the first polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain a double-layer polymer solid electrolyte layer.

[0065] It should be noted that the sum of the masses of the two parts of the second photoinitiator is equal to the mass of the first photoinitiator in the raw material of the second polymer solid electrolyte layer.

[0066] In other possible embodiments, the preparation method may also include the following steps:

[0067] A second reaction monomer A, a second reaction monomer B, a second lithium salt and a part of a second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, a second crosslinking agent, another part of the second photoinitiator, a second carbonate plasticizer and a fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain a second polymer solid electrolyte layer.

[0068] A first reaction monomer A, a first reaction monomer B, a first lithium salt and a portion of a first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, a first crosslinking agent, another portion of the first photoinitiator, a first carbonate plasticizer and a nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is applied to the surface of a second polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain a double-layer polymer solid electrolyte layer.

[0069] In the present application, a double-layer polymer solid electrolyte is prepared by ultraviolet light curing, and no volatile solvents are used, which has the advantages of safety and environmental protection. At the same time, it also has the advantages of low preparation cost and high preparation efficiency. In addition, there are many specific process forms (that is, the first polymer solid electrolyte layer can be prepared first, or the second polymer solid electrolyte layer can be prepared first), and more feasible implementation methods can be provided (the present application embodiment is explained by taking the preparation of the first polymer solid electrolyte layer as an example).

[0070] It should be noted that when the raw material of the first polymer solid electrolyte layer and the raw material of the second polymer solid electrolyte layer differ only in the plasticizer, the formed first polymer matrix and the second polymer matrix are exactly the same, then the polymer matrix can be prepared in one step, and then the polymer matrix can be divided into two parts, that is, the first polymer matrix and the second polymer matrix are simultaneously prepared in one step; when there are multiple differences between the raw material of the first polymer solid electrolyte layer and the raw material of the second polymer solid electrolyte layer, the first polymer matrix and the second polymer matrix are prepared separately, and the specific preparation method can be adjusted according to actual needs.

[0071] It should be noted that when the first polymer matrix and the second polymer matrix are prepared in a step-by-step manner, the first polymer matrix may be prepared first, or the second polymer matrix may be prepared first, or the first polymer matrix and the second polymer matrix may be prepared simultaneously.

[0072] It should be noted that the method of “curing the first polymer solid electrolyte slurry under ultraviolet light to obtain a first polymer solid electrolyte layer” is not limited. For example, the first polymer solid electrolyte slurry may be transferred to a mold and then cured under ultraviolet light to obtain the first polymer solid electrolyte layer; or the first polymer solid electrolyte slurry may be coated on a substrate and then cured under ultraviolet light to obtain the first polymer solid electrolyte layer, and then the substrate may be removed.

[0073] As an example, the first mixed solution is placed under ultraviolet light for reaction until the viscosity of the first mixed solution is 10000-15000 mPa.s, for example but not limited to the viscosity of any one of 10000 mPa.s, 11000 mPa.s, 12000 mPa.s, 13000 mPa.s, 14000 mPa.s and 15000 mPa.s or a range between any two of them; and / or, the second mixed solution is placed under ultraviolet light for reaction until the viscosity of the second mixed solution is 10000-15000 mPa.s, for example but not limited to the viscosity of any one of 10000 mPa.s, 11000 mPa.s, 12000 mPa.s, 13000 mPa.s, 14000 mPa.s and 15000 mPa.s or a range between any two of them.

[0074] In this embodiment, during the curing reaction of the mixed solution under ultraviolet light, the viscosity of the mixed solution reaches a set range, so that the prepared corresponding polymer solid electrolyte layer has a relatively ideal ionic conductivity.

[0075] It should be noted that the steps not specifically described in the process of preparing a double-layer polymer solid electrolyte by UV curing can be arranged according to conventional selections in the art.

[0076] As an example, the wavelength of the ultraviolet light is 300-400 nm, for example but not limited to any one of 300 nm, 320 nm, 340 nm, 360 nm, 380 nm and 400 nm or a range between any two of the wavelengths.

[0077] In a third aspect, an embodiment of the present application provides a lithium-ion battery, comprising a double-layer polymer solid electrolyte provided in the embodiment of the first aspect, wherein the first polymer solid electrolyte layer is in contact with the positive electrode of the battery, and the second polymer solid electrolyte layer is in contact with the negative electrode of the battery.

[0078] In the present application, the lithium-ion battery includes a double-layer polymer solid electrolyte as provided in the first aspect embodiment, wherein the double-layer polymer solid electrolyte has a high ionic conductivity and is compatible with a high-voltage battery positive electrode and a low-voltage lithium metal negative electrode, so that the battery has relatively excellent cycle performance and higher capacity.

[0079] The features and performances of the present application are further described in detail below in conjunction with the embodiments, wherein the raw materials for the first polymer solid electrolyte layer and the raw materials for the second polymer solid electrolyte layer differ only in the type of plasticizer, and the types and amounts of the remaining functional components are the same, and the first polymer matrix and the second polymer matrix are simultaneously prepared by a one-step method.

[0080] Example 1

[0081] The present invention provides a method for preparing a double-layer polymer solid electrolyte, comprising the following steps:

[0082] S1: 37.5 parts of ethoxyethyl acrylate (reaction monomer A), 37.5 parts of butyl hexafluoroacrylate (reaction monomer B), 22.5 parts of lithium bis(trifluoromethanesulfonyl)imide (lithium salt), 2.25 parts of lithium difluorooxalatoborate (lithium salt) and 0.25 parts of 1-hydroxycyclohexylphenyl ketone (photoinitiator) are mixed evenly to form a uniform liquid, and the obtained uniform liquid is placed under a 350nm ultraviolet lamp for reaction. When the viscosity of the liquid rises to 12000mPa.s, the ultraviolet lamp is turned off, and stirring is continued until the temperature reaches room temperature to obtain a polymer matrix (i.e., a first polymer matrix and a second polymer matrix).

[0083] S2: half of the polymer matrix, 3 parts of polyethylene glycol diacrylate (cross-linking agent), 0.5 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 33.5 parts of succinonitrile (nitrile plasticizer) and 8 parts of propylene carbonate (ester plasticizer) are mixed evenly to obtain the first polymer solid electrolyte slurry, which is then coated on PET and placed under 350nm ultraviolet light for curing to obtain the first polymer solid electrolyte layer.

[0084] S3: The other half of the polymer matrix, 2.9 parts of polyethylene glycol diacrylate (cross-linking agent), 0.4 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 16.3 parts of fluoroethylene carbonate (fluorinated plasticizer) and 24.4 parts of propylene carbonate (acid ester plasticizer) are mixed evenly to obtain a second polymer solid electrolyte slurry, which is then coated on the first polymer solid electrolyte layer and cured under 350nm ultraviolet light. The PFT substrate is then removed to obtain a double-layer polymer solid electrolyte layer.

[0085] Example 2

[0086] The present invention provides a method for preparing a double-layer polymer solid electrolyte, comprising the following steps:

[0087] S1: 46 parts of ethoxyethyl acrylate (reaction monomer A), 30.7 parts of butyl hexafluoroacrylate (reaction monomer B), 23.2 parts of lithium bis(trifluoromethanesulfonyl)imide (lithium salt) and 0.1 parts of 1-hydroxycyclohexyl phenyl ketone (photoinitiator) are mixed evenly to form a uniform liquid, and the obtained uniform liquid is placed under a 350nm ultraviolet lamp for reaction. When the viscosity of the liquid rises to 12000mPa.s, the ultraviolet lamp is turned off, and stirring is continued until the temperature reaches room temperature to obtain a polymer matrix (i.e., a first polymer matrix and a second polymer matrix).

[0088] S2: half of the polymer matrix, 3 parts of polyethylene glycol diacrylate (cross-linking agent), 0.5 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 25 parts of succinonitrile (nitrile plasticizer) and 16.5 parts of propylene carbonate (ester plasticizer) are mixed evenly to obtain the first polymer solid electrolyte slurry, which is then coated on PET and placed under 350nm ultraviolet light for curing to obtain the first polymer solid electrolyte layer.

[0089] S3: The other half of the polymer matrix, 3 parts of polyethylene glycol diacrylate (cross-linking agent), 0.5 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 12.5 parts of fluoroethylene carbonate (fluorinated plasticizer) and 29 parts of propylene carbonate (acid ester plasticizer) are mixed evenly to obtain a second polymer solid electrolyte slurry, which is then coated on the first polymer solid electrolyte layer and cured under 350nm ultraviolet light. The PFT substrate is then removed to obtain a double-layer polymer solid electrolyte layer.

[0090] Example 3

[0091] The present invention provides a method for preparing a double-layer polymer solid electrolyte, comprising the following steps:

[0092] S1: 37.5 parts of ethoxyethyl acrylate (reaction monomer A), 37.5 parts of butyl hexafluoroacrylate (reaction monomer B), 22.5 parts of lithium bis(trifluoromethanesulfonyl)imide (lithium salt), 2.25 parts of lithium difluorooxalatoborate (lithium salt) and 0.25 parts of 1-hydroxycyclohexylphenyl ketone (photoinitiator) are mixed evenly to form a uniform liquid, and the obtained uniform liquid is placed under a 350nm ultraviolet lamp for reaction. When the viscosity of the liquid rises to 12000mPa.s, the ultraviolet lamp is turned off, and stirring is continued until the temperature reaches room temperature to obtain a polymer matrix (i.e., a first polymer matrix and a second polymer matrix).

[0093] S2: half of the polymer matrix, 2.6 parts of polyethylene glycol diacrylate (cross-linking agent), 0.4 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 40 parts of succinonitrile (nitrile plasticizer) and 4 parts of propylene carbonate (ester plasticizer) are mixed evenly to obtain the first polymer solid electrolyte slurry, which is then coated on PET and placed under 350nm ultraviolet light for curing to obtain the first polymer solid electrolyte layer.

[0094] S3: The other half of the polymer matrix, 3 parts of polyethylene glycol diacrylate (cross-linking agent), 0.5 parts of 2,2-dimethoxy-phenylacetophenone (photoinitiator), 20.75 parts of fluoroethylene carbonate (fluorinated plasticizer) and 20.75 parts of propylene carbonate (acid ester plasticizer) are mixed evenly to obtain a second polymer solid electrolyte slurry, which is then coated on the first polymer solid electrolyte layer and cured under 350nm ultraviolet light. The PFT substrate is then removed to obtain a double-layer polymer solid electrolyte layer.

[0095] Comparative Example 1

[0096] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which differs from Example 1 only in that all succinonitrile (nitrile plasticizer) is replaced by propylene carbonate (ester plasticizer).

[0097] Comparative Example 2

[0098] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which is different from Example 1 only in that all succinonitrile (nitrile plasticizer) is replaced by vinylene carbonate.

[0099] Comparative Example 3

[0100] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which differs from Example 1 only in that all fluoroethylene carbonate (fluorinated plasticizer) is replaced by propylene carbonate (acid ester plasticizer).

[0101] Comparative Example 4

[0102] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which is different from Example 1 only in that all fluoroethylene carbonate (fluorinated plasticizer) is replaced by ethylene carbonate.

[0103] Comparative Example 5

[0104] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which differs from Example 1 only in that butyl hexafluoroacrylate (reaction monomer B) is completely replaced by ethoxyethyl acrylate (reaction monomer A).

[0105] Comparative Example 6

[0106] The comparative example of the present application provides a method for preparing a double-layer polymer solid electrolyte, which differs from Example 1 only in that ethoxyethyl acrylate (reaction monomer A) is completely replaced by butyl hexafluoroacrylate (reaction monomer B).

[0107] Test example

[0108] Ionic conductivity testing of materials

[0109] Test method:

[0110] The polymer electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were assembled into devices and subjected to ion conductivity tests. Specifically, in an argon-protected glove box, the polymer electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were placed between two pieces of stainless steel, and then loaded into a button battery shell to form a test device. The test conditions were: test temperature of 25°C, scan rate of 1mV / s, frequency range of 1Hz to 1MHz, and the test results were statistically reported in Table 1.

[0111] Electrochemical window testing of materials

[0112] Test method:

[0113] The polymer electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were assembled into devices and subjected to electrochemical window tests. Specifically, in an argon-protected glove box, the polymer electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were placed between stainless steel and a lithium sheet, wherein the first polymer solid electrolyte layer was in contact with the stainless steel, and the second polymer solid electrolyte layer was in contact with the lithium sheet, and then placed in a button battery shell to form a test device, and the test conditions were: a scan rate of 1 mV / s, a test voltage range of 2 to 6 V, and then the test results were statistically recorded in Table 1.

[0114] Battery electrical performance test

[0115] Test method:

[0116] The polymer electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were assembled into devices and the discharge specific capacity and cycle performance thereof were tested. Specifically:

[0117] S1 mixes LiFePO4 (positive electrode active material), conductive carbon black (conductive agent) and polyvinylidene fluoride (binder) in a mass ratio of 80:10:10, disperses in N-methyl-2-pyrrolidone to obtain positive electrode slurry; then, the positive electrode slurry is evenly coated on both sides of the aluminum foil; then, after drying, calendering and vacuum drying in sequence, the dried material is cut into discs with a diameter of 16 mm by a cutting machine to obtain positive electrode sheets.

[0118] S2 is prepared by mixing graphite (negative electrode active material), conductive carbon black (conductive agent) and carboxymethyl cellulose (binder) in a mass ratio of 90:5:5, and dispersing the mixture in deionized water to obtain a negative electrode slurry; then, the negative electrode slurry is evenly coated on one side of a carbon-coated copper foil; then, the mixture is dried, rolled and vacuum dried in sequence, and a cutting machine is used to cut the dried material into discs with a diameter of 16 mm to obtain a negative electrode sheet.

[0119] S3 stacks and assembles the prepared positive electrode sheet, negative electrode sheet and polymer solid electrolyte layers prepared in Examples 1 to 3 and Comparative Examples 1 to 6 in sequence, wherein the first polymer solid electrolyte layer contacts the positive electrode of the battery, and the second polymer solid electrolyte layer contacts the negative electrode of the battery. Then, the stacked batteries are assembled in a battery casing, and a battery is obtained after a capacity test.

[0120] The test steps for relevant electrical properties are as follows:

[0121] (1) Discharge specific capacity test

[0122] At 60°C, the battery is charged to 3.8V at 2C constant current, then allowed to stand for 5 minutes, and then discharged to 2.5V at 2C constant current, and then allowed to stand for 5 minutes. This is a charge and discharge cycle, and the discharge specific capacity this time is recorded as the discharge specific capacity of the battery in the first cycle.

[0123] (2) Battery capacity retention test after 200 cycles at 60°C:

[0124] At 60°C, the battery cell is first charged to 3.8V at a constant current of 1C, and then discharged to 2.5V at a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The battery cell is subjected to multiple cycle charge and discharge tests in the above manner, and the discharge capacity of the 200th cycle is detected, and the capacity retention rate of the battery cell after the cycle is calculated by the following formula. Capacity retention rate of the battery after 200 cycles (%) = [discharge capacity of the 200th cycle / discharge capacity of the first cycle] × 100%.

[0125] Table 1

[0126]

[0127] Referring to Table 1, it can be seen from the test results of Examples 1 to 3 and Comparative Examples 1 to 6 that the polymer solid electrolyte layer is prepared according to the preparation process provided in the embodiments of the present application, and the prepared polymer solid electrolyte layer has a higher ionic conductivity and a higher electrochemical window, so that the prepared battery has a relatively excellent discharge specific capacity and capacity retention rate.

[0128] It can be seen from the test results of Example 1 and Comparative Examples 1 to 2 that when the composite system of nitrile plasticizers and carbonate plasticizers is used as the plasticizer in the first polymer solid electrolyte, compared with the plasticizer containing no nitrile plasticizer, the polymer solid electrolyte layer corresponding to the former has higher ionic conductivity and higher electrochemical window, so that the prepared battery has a better discharge specific capacity and capacity retention rate.

[0129] It can be seen from the test results of Example 1 and Comparative Examples 3 to 4 that when the composite system of fluorine-containing plasticizer and carbonate plasticizer is used as the plasticizer in the second polymer solid electrolyte, compared with the plasticizer without fluorine-containing plasticizer, the polymer solid electrolyte layer corresponding to the former has higher ionic conductivity and higher electrochemical window, so that the prepared battery has better discharge specific capacity and capacity retention rate.

[0130] It can be seen from the test results of Example 1 and Comparative Examples 5 to 6 that when a composite system of an acrylate monomer containing an ethoxy group and an acrylate monomer containing a fluorinated group is used as a reaction monomer, the corresponding polymer solid electrolyte layer has a higher ionic conductivity, so that the prepared battery has a relatively excellent discharge specific capacity and capacity retention rate.

[0131] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A double-layer polymer solid electrolyte, characterized in that: The invention comprises a first polymer solid electrolyte layer for contacting with a positive electrode and a second polymer solid electrolyte layer for contacting with a negative electrode which are stacked and distributed; The raw materials of the first polymer solid electrolyte layer include, by weight: 4 to 30 parts of a first reaction monomer A, 5 to 25 parts of a first reaction monomer B, 2 to 10 parts of a first cross-linking agent, 0.1 to 1.1 parts of a first photoinitiator, 5 to 15 parts of a first lithium salt, 1 to 20 parts of a first carbonate plasticizer, and 20 to 45 parts of a nitrile plasticizer; The raw materials of the second polymer solid electrolyte layer include, by weight: 4 to 30 parts of a second reactive monomer A, 5 to 25 parts of a second reactive monomer B, 2 to 10 parts of a second crosslinking agent, 0.1 to 1.1 parts of a second photoinitiator, 5 to 15 parts of a second lithium salt, 1 to 35 parts of a second carbonate plasticizer, and 10 to 35 parts of a fluorine-containing plasticizer; The first reactive monomer A and the second reactive monomer A are both acrylate monomers containing ethoxy groups, and the first reactive monomer B and the second reactive monomer B are both acrylate monomers containing fluorinated groups.

2. The double-layer polymer solid electrolyte according to claim 1, characterized in that: The nitrile plasticizer is selected from at least one of succinonitrile, adiponitrile, tetracyanoethylene, ethylene glycol dipropionitrile ether, sulfonyl dipropionitrile, 1,3,6-hexanetrinitrile and 1,2,5-pentanetrinitrile.

3. The double-layer polymer solid electrolyte according to claim 1, characterized in that: The fluorine-containing plasticizer is at least one selected from fluoroethylene carbonate, ethyl trifluoroacetate, trifluoroethyl trifluoroacetate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorinated methanesulfonimide, difluoroethane and fluorinated malonate.

4. The double-layer polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The first carbonate plasticizer and the second carbonate plasticizer are independently selected from at least one of ethylene carbonate, vinylene carbonate, dimethyl carbonate, dipropyl carbonate, ethylene carbonate, butylene carbonate, ethyl methyl carbonate and propylene carbonate.

5. The double-layer polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The first reactive monomer A and the second reactive monomer A are independently selected from at least one of ethoxyethyl acrylate, ethoxylated tetrahydrofuran acrylate, ethoxylated trimethylol triacrylate, 3-ethoxyethyl acrylate, 2-phenoxyethyl acrylate and 2-vinyloxyethoxy acrylate.

6. The double-layer polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The first reactive monomer B and the second reactive monomer B are independently selected from at least one of butyl hexafluoroacrylate, propyl tetrafluoroacrylate, ethyl trifluoroacrylate, dodecafluoroheptyl methacrylate, perfluoroalkylethyl acrylate and N-methylperfluorohexylsulfonamide ethyl acrylate.

7. The double-layer polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: Satisfy at least one of the following conditions (1) to (3): (1) the first cross-linking agent and the second cross-linking agent are independently selected from at least one of diethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate and ethoxylated bisphenol diacrylate; (2) the first photoinitiator and the second photoinitiator are independently selected from at least one of 2,2-dimethoxy-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl chloride-diphenylphosphine oxide, 2,2-dimethoxy-phenylacetophenone and 2-hydroxy-2-methyl-1-phenyl-1-propanone; (3) The first lithium salt and the second lithium salt are independently selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium hexafluorophosphide, lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium bis(difluorosulfonyl)imide.

8. A method for preparing a double-layer polymer solid electrolyte as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: The first reaction monomer A, the first reaction monomer B, the first lithium salt and a part of the first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, the first crosslinking agent, another part of the first photoinitiator, the first carbonate plasticizer and the nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain the first polymer solid electrolyte layer; The second reactive monomer A, the second reactive monomer B, the second lithium salt and a part of the second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, the second crosslinking agent, another part of the second photoinitiator, the second carbonate plasticizer and the fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is applied to the surface of the first polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain the double-layer polymer solid electrolyte layer; or, The second reactive monomer A, the second reactive monomer B, the second lithium salt and a part of the second photoinitiator are mixed to obtain a second mixed solution; the second mixed solution is placed under ultraviolet light for reaction to obtain a second polymer matrix; the second polymer matrix, the second crosslinking agent, another part of the second photoinitiator, the second carbonate plasticizer and the fluorine-containing plasticizer are mixed to obtain a second polymer solid electrolyte slurry; the second polymer solid electrolyte slurry is placed under ultraviolet light for curing to obtain the second polymer solid electrolyte layer; The first reaction monomer A, the first reaction monomer B, the first lithium salt and a part of the first photoinitiator are mixed to obtain a first mixed solution; the first mixed solution is placed under ultraviolet light for reaction to obtain a first polymer matrix; the first polymer matrix, the first cross-linking agent, another part of the first photoinitiator, the first carbonate plasticizer and the nitrile plasticizer are mixed to obtain a first polymer solid electrolyte slurry; the first polymer solid electrolyte slurry is applied to the surface of the second polymer solid electrolyte layer and placed under ultraviolet light for curing to obtain the double-layer polymer solid electrolyte layer.

9. The preparation method according to claim 8, characterized in that: The step of placing the first mixed solution under ultraviolet light for reaction is performed until the viscosity of the first mixed solution is 10000-15000 mPa.s; and / or the step of placing the second mixed solution under ultraviolet light for reaction is performed until the viscosity of the second mixed solution is 10000-15000 mPa.s.

10. A lithium ion battery, characterized in that: It comprises a double-layer polymer solid electrolyte as claimed in any one of claims 1 to 7, wherein the first polymer solid electrolyte layer is in contact with the positive electrode of the battery, and the second polymer solid electrolyte layer is in contact with the negative electrode of the battery.

Citation Information

Patent Citations

  • Composite solid electrolyte and preparation method thereof and all-solid-state lithium ion battery containing composite solid electrolyte

    CN110729513A

  • Polymer solid electrolyte and preparation method thereof, lithium battery and electric equipment

    CN118398886A

  • Porous Polymeric Electrolytes Comprising Vinylidenefluoride and Polyacrylate Polymers and Process for Preparing theSame

    KR1020010010675A

  • Porous Film Type Solvent-Free Polymer Electrolyte Filled with Oligomer / Prepolymer Electrolyte and Secondary Battery Employing the Same

    US20080038642A1

Cited By

  • Preparation method of polysulfone-polyether double-layer solid electrolyte

    CN120809946A

  • Polymer electrolyte and preparation method and application thereof

    CN120824418A

  • A polymer electrolyte, its preparation method and application

    CN120824418B

  • Solid elastomer electrolyte with layered structure as well as preparation method and application of solid elastomer electrolyte

    CN121546137A

  • A layered solid elastomeric electrolyte and its preparation method and application

    CN121546137B